PERAN SERTA MASYARAKAT DALAM PERKARA TINDAK PIDANA NARKOTIKA - Adista Dwi Lestari (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACT Indonesia is a developing country where increasing welfare starting from Natural Resources (SDA), Human Resources to the field of medicine and health services must be improved. Narcotics are also used for experiments and research organized by the government in the interests of science and obtain permission from the Minister of Health. However, the increasingly widespread abuse and illicit trafficking of narcotics can not be separated from one of the characteristics of the item which is causing destructive addiction in terms of use not for treatment and illegally.            In this writing the role of witnesses is very important as the initial information of law enforcement parties as witnesses listed in Article 1 point 26 of the Criminal Procedure Code in giving information before the court must be given witness protection. The need for witnesses and victims to get protection from the security, medical, social, psychological, and financial aspects seems to have been indisputable.   The Role of Society in Preventing Narcotics Crimes in Samarinda. Related to the prevention of narcotics in Samarinda, there are a number of steps that must be taken so that prevention will be carried out effectively. Related to the prevention of narcotics in the city of Samarinda, researchers see so far going very well, but apart from that so that the law governing community participation is further strengthened and applied properly. Because legal awareness and adherence to the rights and obligations in preventing narcotics, affect the effectiveness of prevention itself. Keywords: The role of the community in uncovering Narcotics